2020
DOI: 10.21608/ejvs.2019.20398.1140
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Balanites Aegyptiaca Fruit’s Ethanol Extract in Egyptian Baladi Goats Experimentally Infected with Haemonchus Contortus: Blood Serum Biochemical, Oxidative Stress Markers and Pathological Studies

Abstract: the native breed of goats that is located in the Nile Delta and along the Nile Valley is known as Baladi goats. Amongst other breeds of goats, the Baladi goats have a great economic value [1] and play an essential role in the economy of small, marginal farmers and landless labourers in Egypt [2]. T HE THERAPEUTIC effect of Balanites aegyptiaca fruit's ethanolic extract (BAF-EE) in goats experimentally infected with Haemonchus contortus (H. contortus) was evaluated. Serum biochemical parameters, tissue oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Also, the TBARS value did not differ among group I and III. Our result is in accordance to Jaheed et al (2020) who found significantly higher values of MDA in albendazole treated group compared to the herbal treated group in Haemonchus infected goats and Dimitrijevic et al (2012) who reported increased MDA concentration, both in the presence of Strongyle infected sheep and albendazole treatment, when compared to the control group negative for parasites. Locatelli et al (2004) reported that albendazole provoked an oxidative stress condition, demonstrated through the elevation of TBARS contents suggesting albendazole as a strong ROS and RNS generator.…”
Section: Tbarssupporting
confidence: 91%
“…Also, the TBARS value did not differ among group I and III. Our result is in accordance to Jaheed et al (2020) who found significantly higher values of MDA in albendazole treated group compared to the herbal treated group in Haemonchus infected goats and Dimitrijevic et al (2012) who reported increased MDA concentration, both in the presence of Strongyle infected sheep and albendazole treatment, when compared to the control group negative for parasites. Locatelli et al (2004) reported that albendazole provoked an oxidative stress condition, demonstrated through the elevation of TBARS contents suggesting albendazole as a strong ROS and RNS generator.…”
Section: Tbarssupporting
confidence: 91%